UM OLHAR SEMIÓTICO SOBRE O PANTANAL E SEUS COSTUMES EM TELAS DE ARTISTAS SUL-MATO-GROSSENSES - Évelyn Coelho Paini Webber (2023)
The Pantanal, in Brazil, runs through the states of Mato Grosso and Mato Grosso do Sul and is home to various species of birds, fish, mammals, reptiles and plants; some of which are even at risk of extinction, such as the hyacinth macaw, the dorado, the giant anteater and the jaguar, to name but a few. However, the Pantanal is not restricted to its diversity of fauna and flora, as there is a people there who also bear its marks, for example, the peão pantaneiro, with customs that represent Pantanal culture and make up the culture of the state of Mato Grosso, through food (arroz carreteiro), drink (the traditional tereré), the use of plants and devotion to the saints. There is another aspect of Mato Grosso culture that is influenced by the Pantanal: art. There are many artists who have established the artistic identity of Mato Grosso do Sul with their canvases and sculptures featuring unique aspects of the Pantanal, the Pantanal man and/or the indigenous peoples who occupy this area. Thus, based on studies of Greimasian semiotics and one of its offshoots, the plastic semiotics thought up by Floch (1985), we aim to analyze the canvases of three artists: Cleir Ávila, Jorapimo and Marlene Mourão Mar (Peninha), in order to glimpse how meanings are constructed on the level of content, through the generative path of meaning, and on the level of expression, through the eidetic, topological and chromatic dimensions. In addition, we seek to study Pantanal culture as well as publicize art from Mato Grosso do Sul and its artists. Greimasian semiotics understands the text as an object of meaning and communication, so it initially focused on verbal texts, analyzing them through their generative path of meaning (and its three levels, fundamental, narrative and discursive); then, later, other scholars such as Floch (1985) and Oliveira (2004) dealt with non-verbal and/or syncretic texts, using plastic semiotics and its dimensions in the analyses. Plastic semiotics uses four categories created by Floch (1985) to examine the plane of expression of non-verbal objects: eidetic, topological, chromatic and materic plastic categories. Furthermore, through plastic semiotics we can establish relationships between the categories of the plane of expression and the plane of content through semisymbolism. So, when we carried out the study, we understood that discussing South Mato Grosso culture and analyzing Pantanal art contains deeper aspects, such as a review of the very concept of art and what makes up what we call Pantanal culture, strongly linked to Pantanal customs (food, drink, costumes, use of plants as medicine and religiosity), which reinforced the interdiscursiveness present in the research that permeates from the choice of artists to the analysis. In addition, we were able to understand how meanings are constructed on the canvases through the semantics of the fundamental and discursive level and the topological, eidetic and chromatic categories of the plane of expression. We noticed that sometimes the paintings, which have the Pantanal as their main theme, act as syncretic, dialoguing with their titles and sometimes as individual and unique plastic objects in the composition of meanings. We were also able to identify some semi-symbolic relationships on the canvases (categories from the plane of expression with categories from the plane of content), as well as oppositions of nature vs. culture, humanity vs. animality and humanity vs. divinity, which show us the strong connection between Pantanal culture, the environment and the beliefs of the people who live there.